Comparative effectiveness of surgical and Non-surgical management for patients with single level lumbar disc herniation in terms of symptom severity and quality of life - Sangoli, Shashank (Nepal Journal of Neuroscience, 2021)
Aim: Sciatica is one of the most severe form of low back pain, with a lifetime prevalence of approximately 30 percent. To assess the short-term and long-term efficacy of surgical and conservative care in the incidence of sciatic symptoms and quality of life in standard clinical settings in patients with lumbar disc herniation. Material and method: It is a retrospective study conducted at Medical Trust Hospital, Kochi who underwent micro lumbar discectomy for single level lumbar disc herniation, and of those with the same diagnosis but who refused surgery or were still waiting for the surgery to be scheduled. The patients were divided into two groups as Group A- treated surgically and Group B – awaiting for surgery and managed non-surgically. Cases between 20-60 years of age, male or female, with low back pain and lower limb radiculopathy, positive signs of root tension (SLRT between 30-70 degrees or severe femoral root stress), associated neurological dysfunction (with respect to corresponding abnormal reflexes, reduced sensation in dermatomal distribution or weakness in myotomal distribution) and multiple disc herniation cases if only one of the level was symptomatic, were included. The study excluded patients with scoliosis of more than 15 degrees, segmental instability, spondylolisthesis, spine or tumor infection, psychiatric disease, refusal of patients and age < 20 and > 60 years. All patients recruited had to fill the consent and a clinical evaluation by means of established questionnaires which included the Short Form 36 (SF36), 16 the Oswestry Disability Index (ODI), 17 and the visual analog scale for pain (VAS). Then were grouped into: Group A, for those who had already undergone surgical treatment and Group B, those awaiting surgery. Results:Total 60 patients fulfilling the inclusion criteria were included in present study. Mean age of the patients in Group A was 36.7 ± 5.8 and in Group B was 37.01 ± 5.56 years. Male preponderance was observed in our study with male to female ratio of 1.7:1. At the time of admission, patients in both the groups suffered similar scale of pain and agony. The VAS and ODI did not show significant difference in the pain and disability in both group of patients. During follow-up of 6month and 2 years, surgically treated patients showed a significant improvement in the scores of VAS and ODI. Also the SF-36 also showed a similar results and was better in patients treated by surgery contrary with conservative treatment. Conclusion:the study concluded with positive benefits from surgery with a reduction in pain reported in the lower limbs (VAS leg with p<0.05) and improved function (Oswestry with p<0.05); however, it did not show any much significant change in quality of life according to the SF-36 scale.